Les dispositifs ULIS au collège : quelles articulations entre la classe et le regroupement spécialisé ? - Frédéric Dupré (Nantes Université, 2019)
Our object of study concerns ULIS devices (localized units for inclusive education) within the French college. These allow students recognized as institutionally disabled to have an education in an ordinary classroom while benefiting from a support system. The organization of these devices places students at two didactic systems: the one of the ordinary class and that of the ULIS group. Through two case studies, we study the links that emerge between the main didactic system (mathematics class) and the auxiliary didactic system (specialized grouping) in order to highlight actions that make it possible to synchronize these two didactic systems.